Prospects and opportunities for exports of dairy products from India - KUMAR, ANJANI; RAI, D V; CHOUDHARY, KHYALI RAM (The Indian Journal of Animal Sciences, 2011)
The economic policy reforms triggered in India in 1991 were oriented towards liberalization and integration with the world economy. These policy initiatives of reforms and economic liberalization widened the market opportunities for international trade including the dairy products. In this context, this paper examines the issues of trade possibilities for India, in view of growing domestic consumption, augmented supply and growing international market for dairy products. The study revealed that growth in Indian dairy sector has been impressive and if the existing growth rate can be sustained, India can pursue export of dairy products more vigorously. The projected demand scenarios for domestic requirement of dairy products lend credence to this optimism. It has been clearly brought out that the dairy production is competitive in comparison with other countries. India further has a geographical advantage to serve milk deficit areas in neighbouring countries. The demand for milk products in these deficit countries is expected to be growing. India needs to capitalize on these advantages by improving quality and hygiene standards of the dairy products and bringing more efficiency in milk production and processing. India needs to develop more competitiveness in products which are being imported in countries like Sri Lanka, Bangladesh and Nepal from other developed countries. For export to SAARC countries even some more liberal export policies may be explored.